Influences on perceived stress among undergraduates during COVID-19 induced transition to open distance learning: a multiple linear regression analysis / Nurhasniza Idham Abu Hasan ... [ et al.] - Abu Hasan, Nurhasniza Idham; Ganggayah, Mogana Darshini; Jamian, Nurul Husna; Zamin, Norshuhani (Universiti Teknologi MARA, Perak, 2023)
Due to the COVID-19 pandemic, numerous institutions, encompassing both public and private universities, have shifted their focus towards open and distance learning (ODL) as a replacement method of teaching. This rapid evolution of the education system has brought to the forefront a concerning increase in students' mental health issues. Therefore, this study endeavors to identify the factors that contribute to the perceived stress levels experienced by undergraduate students during ODL. A total of 630 undergraduate students were involved in this research, chosen using a convenience sampling approach. The survey instrument encompassed inquiries about demographic characteristics and employed the Perceived Stress Scale-10 to gauge stress levels. Multiple Linear Regression analysis was employed to scrutinize the data in pursuit of our research objective. The findings underscore the significance of several factors in influencing perceived stress among undergraduate students in the ODL context. Specifically, network condition, level of semester, and gender emerged as noteworthy contributors to the perceived stress experienced by undergraduate students.